Indução de mania ou hipomania por antidepressivos prosserotonérgicos no transtorno afetivo bipolar e sua associação com o polimorfismo 5-HTTLPR - Alexandre de Aguiar Ferreira (2008)
The occurrence of mania/hypomania during antidepressant treatment is a key issue in the clinical management of bipolar disorder (BD). The serotonin transporter gene is a candidate to be associated with antidepressant-induced mania/hypomania (AIM) in some patients. This gene has a polymorphism within the promoter region (5-HTTLPR) with two allelic forms, the long (L) and the short (S) variants. In the present study, it was investigated the role of the 5-HTTLPR gene polymorphism as a potential genetic predictor for mania or hypomania induced by proserotonergic antidepressant treatment in bipolar patients. In addition, it was studied the mood stabilizer effect in this association. A case-control study was performed to compare 5-HTTLPR genotype and allelic frequencies between 43 patients with a DSM-IV diagnosis of BD, with at least one manic/hypomanic episode associated with treatment with proserotonergic antidepressants (AIM+) and 69 unrelated, matched bipolar patients, who had been exposed to proserotonergic antidepressants without development of manic symptoms (AIM-). Furthermore, we performed this comparison between a subgroup of 23 AIM+ patients that, when they presented AIM, were not using mood stabilizer (AIM+*) and 25 AIM- patients who used antidepressant without the concomitant use of a mood stabilizer (AIM-*). 5-HTTLPR genotyping was performed using PCR. No significant differences were found between AIM+ and AIM-. Within the subgroups, our results show that S-carriers (LS +SS genotypes) are more prone to make a manic/hypomanic episode associated with antidepressant (P=0.0179). The 5-HTTLPR polymorphism may be considered a predictor of abnormal response to antidepressant in patients with BD, but this action is influenced by the presence of a mood stabilizer. Such observations reinforce that a correct diagnosis of bipolarity before the beginning of the treatment is essential, mainly for S-carriers patients.